Death and funeral practices in Aotearoa New Zealand - McManus, Ruth (Routledge, Taylor & Francis Group, 2025)
"This book provides a shortform definitive reference text on the landscape and features of Aotearoa New Zealand that underpin its familiar, though country specific, ways of caring for the dead. It provides an account of diverse funerary practices that have taken shape through the various cultures that have settled here. In the backdrop of the colonising history of Aotearoa New Zealand, the book examines the complex legislative framework that separates Māori and non-Māori funerary legislation, and practices. Examining the mixed model of provision spanning municipal, commercial, and private organizations, the book outlines various aspects of funerals, such as the care of the body, funeral arrangements, costs, and what state support is available. It also delves into the two legal ways to manage the dead: burial or cremation, with cremation now the majority option. The book explores the numbers, ownership and locations of crematoria and cemeteries before identifying the new trends influencing death care including sustainability. It then looks at how death is memorialised in Aotearoa New Zealand, including in cemeteries, for war memorialisation and other public commemoration and memorialisation. This book will be of interest to the growing body of local authority planners, researchers and funeral professionals who must be responsive to and provide their services in complex multi-cultural contexts. As the scope of the book is historical and contemporary death practices, it will also appeal to social historians"--